All-fiber passively mode-locked ultrafast laser based on a femtosecond-laser-inscribed in-fiber Brewster device - Huang, Zinan; Huang, Qianqian; Theodosiou, Antreas; Cheng, Xi; Zou, Chuanhang; Dai, Lilong; Kalli, Kyriacos; Mou, Chengbo (My University, 2019)
We report on an in-fiber Brewster device with a 45° tilted fiber grating (TFG) directly written by a plane-by-plane femtosecond laser inscription method. Up to 10 dB polarization-dependent loss was achieved, proving effective polarizing functionality. Furthermore, we employ it as an in-line polarizer to successfully mode lock a fiber laser through the nonlinear polarization rotation technique. A stable soliton pulse train has been generated at 1563.64 nm with a pulse width of 624 fs and pulse energy of 0.42 nJ. With proper polarization adjustment, the laser also can operate in a noise-like regime. The parameters of this kind of 45°-TFG can be flexibly customized owing to the high flexibility and controllability of the femtosecond laser-inscription approach. In particular, such in-fiber polarizing devices inscribed by femtosecond laser inscription without removing the fiber coating are extremely robust for fiber lasers working at a broad wavelength region including the mid-infrared.
Keywords: Femtosecond lasers; Fiber lasers; Passive mode locking; Polarization